Giant incisional hernia containing a large renal cyst. (November 2017) - Wöstemeier, Anna; Perez, Daniel; Dahlem, Roland; Izbicki, Jakob R; Melling, Nathaniel
Abstract : Introduction: Hernias are common surgical diseases. Incidence of incisional hernia depends upon the size and location of the former incision and ranges from 3 to 20 percent. In clinical practice the variability of surgical techniques for hernia repair is great and a wide range of publications are available. Surgery for renal cysts depends on whether they are classified simple or complex. Simple cysts are more common and the majority requires no treatment. Complex renal cysts are associated with an increased risk of malignancy. This is the first report on a giant incisional hernia containing bowl combined with a voluminous renal cyst. Case description: An 80-year-old female diagnosed with a giant incisional hernia combined with a large left renal cyst was referred to our surgical department from a peripheral hospital for hernia repair. Physical examination showed a ventral incisional hernia (50x50cm) extending to the upper thigh with multiple skin lesions and clinical signs of obstipation. CT scan revealed two hernial orifices measuring 13cm and 4.5cm in diameter. The giant hernial sac contained not only incarcerated small and large bowl but also a large left renal cyst containing 3 litres of fluid. Results and Conclusions: We performed a second median laparotomy with complete release of all abdominal adhesions. The renal cyst was resected and its base marsupialized. Hernia repair was achieved by both sided compartment separation as described by Ramirez combined with an intraperitoneal onlay mesh sized 40cmx60cm. Intraoperative measurement of creatinine in the cyst fluid revealed no connection to the urinary tract making further renal surgery unnecessary. By resecting the renal cyst, intraabdominal volume was markedly reduced allowing tension free abdominal wall reconstruction. Histological examination of the cyst, the hernial sacs and the resected skin revealed no surprising findings. Postoperative recovery was uneventful and drains were removed before discharge. Bowel movement started on the third postoperative day. Wound dehiscence was treated by negative pressure wound therapy and no recurrence has yet been detected two months postoperatively. Take home message: Surgical repair of giant incisional hernias is challenging and is associated with significant morbidity and mortality. Individual planning of abdominal wall reconstruction is key for successful treatment and is even the more important in complex hernias with loss of domain or accompanying intraabdominal pathologies.